New antimicrobial diterpenes from Tinospora rumphii - Cruz, Ma. Cecelyn S. (Animo Repository, 2000)
The chloroform extract of the air-dried leaves of Tinospora rumphii Boerl, afforded a new clerodane diterpene, B2, and the known diterpenes B1, tinotufolin D (B5) amd vitexilactone (B3). B1 and B5 are furanoid diterpenes, while B2 is a butenolide diterpene and B3 is a labdane diterpene. The structures of B2 and B5 were elucidated by extensive 1D and 2D NMR spectroscopy and confirmed by UV, IR and Mass Spectrometry. The structures of B1 and B3 were identified by comparison of their 1H NMR spectral data with those reported in the literature.The antimicrobial analysis conducted on B2, B5 and B1 using the agar cup method indicated the following results: B2 was found to inhibit the growth of the fungi Aspergillus niger and Trichophyton mentagrophytes and the bacteria Pseudomonas aeruginosa and Bacillus subtilis, but inactive against Staphyloccocus aureus, Escherichia coli and Candida albicans. B5 inibited the growth of the fungi Aspergillus niger and Trichophyton mentagrophytes and the bacteria Bacillus subtilis but inactive against Staphyloccocus aureus, Escherichia coli, Pseudomonas aeruginosa and Candida albicans. B1 was found to inhibit the growth of the bacteria Bacillus subtilis, but inactive against Aspergillus niger, Trichophyton mentagrophytes Staphyloccocus aureus, Escherichia coli, Pseudomonas aeruginosa and Candida albicans.